The Ease Of Application Of Online Licensing Services In The Investment Service And Integrated Services Of One Door Of Pemalang District - Widuta, Anangga; ., Fitriyah (Journal of Politic and Government Studies, 2018)
This study aims to determine the licensing service in the Pemalang District Investment and One-Stop Service Department by using Electronic Government. Licensing services using Electronic Government in the One-Stop Integrated Investment and Services Office of Pemalang Regency are agencies that pioneered the existence of Electronic Government in Pemalang District.This research uses descriptive research with quantitative approach method. The sampling technique uses Non Probability Sampling using the results data from the questionnaire, where not all population units have the opportunity to be used as research samples.The results showed that access to licensing services in the Investment Office and the One Stop Services of Pemalang Regency was good. With indicators the use of websites on Electronic Government gets 373 in good category, website navigation system gets 400 in good category, visual design gets 415 in good category, service response gets 390 in good category, website content gets 390 in good category , webiste content gets 412 with good category, and accessibility gets 424 with very good category.From these results also get new findings in accessing licensing services using Electronic Government in the Investment and One-Stop Service Department of Pemalang District that there are still many people who want to get licensing services still do not know about Electronic Government. The people who do not know this are still going directly to the Investment Office and One-Stop Services office and manage the permits manually, the process takes longer because the information input is done by limited service personnel.Â Keywords : Electronic Government, Licensing Services